10‐4: A 13.3‐inch 8K x 4K 664‐ppi 120‐Hz 12‐bit Display with Super‐wide Color Gamut for the BT.2020 Standard. Issue 1 (2nd June 2017) - Sasaki, Toshiki; Yamaoka, Ryohei; Nomura, Shiho; Yamamoto, Roh; Takahashi, Kei; Nakamura, Daiki; Aoyama, Tomoya; Ikeda, Hisao; Seo, Satoshi; Yamazaki, Shunpei
Abstract : Newly developed light‐emitting materials and device structure achieved a highly efficient long‐lived white tandem OLED with saturated RGB spectra for a wider color gamut. By combining the OLED devices with a color filter and top emission structure, we successfully fabricated a full‐specification 8K AMOLED panel with the BT.2020 color gamut.